Auriculoterapia na prática da estratégia saúde da família: percepção de usuários e o sentido da oferta por profissionais da saúde - Melquiades, Cynthia Guedes Santiago (2022)
T he objective of this study was to analyze the perceptions and meanings attributed to a uriculotherapy by users and professionals of a Family Health Unit FHU This research is based on the theoretical methodological framework of qualitative research. The scenario was a FHU located at Jo ão Pessoa, Para í ba Eleven users attended at the FHU who unde rwent auriculotherapy treatment and participated in the auriculotherapy group at the FHU were interviewed, data were collected using a semi structured instrumen t. From a meeting with four health professionals, who were part of this care process at the FHU, a conceptual map was built. In addition, professionals were interviewed. For data analys is, Content Analysis was adopted with a thematic approach. For the conceptual map, C ma p T ools ® software was used and the semantic clarity of the propositions was obs erved using the Proportional Clarity Table. The Ethics Committee in Research with Human approve d under number 43517121.8.0000.5188. The information collected on axes of treatment with a uriculotherapy contributed to the analysis and interpretation of the data that emerged th r ee thematic categories: Perception of the integral and holistic care mode Well being with the use of auriculotherapy; Pandemic repercussions relations to auriculotherapy treatment; It all started from our desire to help, to improve because otherwise we would have been without this practice. Health professionals worked from the perspective of re arranging the culture of care, differentiating themselves from biomedicine. In the construction of the conceptual map, the experience of what was lived within the group with the work in auriculotherapy, the team's motivations, strengths and weaknesses face d for the implementation of the auriculotherapy offer at the FHU can be perceived The re ports of users and professionals showed that the practice of auriculotherapy and the formation of the group enhanced the production of care, gave new meaning and strengthened teamwork and promoted the well being of users who brought physical and emotional complaints. The challenges for the implementation of this practice were guided by the need for an expanded look at the management and support for the valorization of auriculotherapy and its offer to users who attend health services.